PENGARUH KEMANDIRIAN BELAJAR DAN LINGKUNGAN PERGAULAN TERHADAP HASIL BELAJAR OTK HUMAS DAN KEPROTOKOLAN SMK NEGERI 3 SURAKARTA - iin khoiriyah; Patni ninghardjanti; Susantiningrum Susantiningrum (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2022)
Abstract The study was aimed to determine (1) the effect of self-regulated learning on students’ learning outcomes of OTKP students grade XII in Public Relations and Protocol Administration subject at SMK Negeri 3 Surakarta in year 2020/2021; (2) the effect of social environment on students’ learning outcomes of OTKP students grade XII in Public Relations and Protocol Administration subject at SMK Negeri 3 Surakarta in year 2020/2021; and (3) the effect of self-regulated learning and social environment on students’ learning outcomes of OTKP students grade XII in Public Relations and Protocol Administration subject at SMK Negeri 3 Surakarta in year 2020/2021. This study was quantitative research with a correlational method. The population of this study was twelfth grade students OTKP of SMK Negeri 3 Surakarta in the 2020/2021 academic year, 102 students. The researcher used incidental sampling with 81 students as the sample. The data were collected using documentation and questionnaires. The data self-regulated learning and social environment were collected using questionnaires, meanwhile the data of students’ learning outcomes were collected using documentation. Then the data were analyzed using a prerequisite test and multiple linear regression analysis using IBM SPSS 22.0 program. This result of study showed that: (1) there was a positive effect of self-regulated learning on student’ learning outcomes of twelfth grade students of OTKP SMK Negeri 3 Surakarta year 2020/2021 with t-value 1,995 > t-table 1,99085; (2) there was a positive effect of social environment on students’ learning outcomes grade XII OTKP students at SMK N 3 Surakarta year 2020/2021 with t-value 2,253 > t-table 1,99085; and (3) there was a positive effect of self-regulated learning and social environment on students’ learning outcomes of  grade XII OTKP students at SMK N 3 Surakarta year 2020/2021 with F-value 13,088 > F-table 3,11.